Comparison of Image Quality Between Virtual Grid And Physical Grid At A Ratio of 10:1 Using Digital Radiography (DR) - Muhammad Irsal; Shinta Gunawati Sutoro; Rafhael Reznandika Yustiyo (Diponegoro University Semarang Indonesia, 2026)
Virtual Grid (VG) in radiology is still rarely used since this technology is still new and literature information is scarce. The objective of this study is to evaluate image quality between virtual grid (VG) and physical grid at a grid ratio of 10:1 using digital radiography (DR). This study employed a descriptive analytical method conducted between June and July 2025 at the Physics and Radiography Laboratory of the Department of Diagnostic Imaging and Radiotherapy, Poltekkes Jakarta II. The equipment used included an X-ray multipurpose, a DR imaging system equipped with a VG at a ratio of 10:1, a physical grid at a ratio of 10:1, Radiant DICOM Viewer software, and a stepwedge. The research preparation involved testing the X-ray machine and DR modalities, followed by exposure at varying tube voltages of 60 kVp, 70 kVp, 80 kVp, and 90 kVp, with three variations in tube current-time: 10 mAs, 16 mAs, and 20 mAs. The obtained images were analyzed using the Radiant DICOM Viewer to assess image quality based on the measured signal difference to noise ratio (SDNR) and figure of merit (FOM). The result identical graphical patterns observed with increases in tube voltage and tube current-time indicate that the VG ratio of 10:1 tends to show improved SDNR and FOM values compared to the physical grid ratio of 10:1 and non-grid configurations. The image quality of the VG with a 10:1 ratio outperforms both the physical grid and non-grid configurations in DR imaging.